2021
DOI: 10.3389/fimmu.2021.670205
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Mast Cell Activation by Cholesterol-Dependent Cytolysins

Abstract: Mast cells are potent immune sensors of the tissue microenvironment. Within seconds of activation, they release various preformed biologically active products and initiate the process of de novo synthesis of cytokines, chemokines, and other inflammatory mediators. This process is regulated at multiple levels. Besides the extensively studied IgE and IgG receptors, toll-like receptors, MRGPR, and other protein receptor signaling pathways, there is a critical activation pathway based on cholesterol-dependent, por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 145 publications
(178 reference statements)
0
5
0
Order By: Relevance
“…VPA decrease MC cytokine production by these TLR2 ligands, in similar way to what is observed in macrophages stimulated with Pam 22 . In addition, we observed that VPA inhibited MC activation with LLO, which activates MC in a TLR2-independent manner 14 , 30 through cholesterol dependent activation 36 mediated by ERK1/2 phosphorylation 49 . These observations indicate that VPA does not affect TLR2 expression in MC and suggest that this compound compromises L.m-mediated MC activation by modulating intracellular activation mechanisms involved in the MC response to this pathogen.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…VPA decrease MC cytokine production by these TLR2 ligands, in similar way to what is observed in macrophages stimulated with Pam 22 . In addition, we observed that VPA inhibited MC activation with LLO, which activates MC in a TLR2-independent manner 14 , 30 through cholesterol dependent activation 36 mediated by ERK1/2 phosphorylation 49 . These observations indicate that VPA does not affect TLR2 expression in MC and suggest that this compound compromises L.m-mediated MC activation by modulating intracellular activation mechanisms involved in the MC response to this pathogen.…”
Section: Discussionmentioning
confidence: 75%
“…In fact, MC initiate the response against Listeria monocytogenes (L.m) by promoting the recruitment of neutrophils to the site of infection in an experimental model of murine listeriosis 9 . Moreover, L.m activates MC by triggering TLR2 and through cholesterol-dependent activation by listeriolysin O (LLO) 14 , 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The classical activation pathway of MCs involves downstream signaling mediated by the high-affinity receptor (FceRI) for IgE on the MC surface. Additionally, MC membranes harbor various receptors activated by their ligands, including cytokine and chemokine receptors, Toll-like receptors (TLRs), and vascular endothelial growth factor receptors [11,12]. Moreover, studies have showed that MCs can selectively release particulate matter through a process known as segmental degranulation.…”
Section: Biological Activity and Activation Of MCmentioning
confidence: 99%
“…Moreover, studies of diverse infections have demonstrated that MCs can detect assault by bacterial cytolytic toxins 12 16 . Based on the latter studies, a common theme emerges, in which MCs respond vigorously to sublytic membrane perturbation that precedes toxin-mediated lysis 16 , 17 . It is unclear whether this mode of sensing also extends to other membrane-interfering events, such as the docking of bacterial secretion machineries to the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%